(untitled) (Research, Society and Development, 2021)
The urbanization process in Fortaleza (Ceará/Brazil) and Florianópolis (Santa Catarina/Brazil) cities had the coastal tourism as one of the main factors of their development. This profile-qualitative and theoretical-theme proofreading survey, aims to discuss the historical and contemporary process of touristic urbanization in Fortaleza and Florianópolis municipalities. It was concluded that it is mandatory to plan and to think about the implications that might occur in the face of the gap alteration motivated by tourism or by any other financial activity.